2020
DOI: 10.29321/maj.2020.000375
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Thiamethoxam 25 Wg Against Sucking Pests in Okra

Abstract: Two field experiments were conducted to test the efficacy of different doses of thiamethoxam against okra sucking pests viz., Aphids, Aphis gossypii; leaf hopper, Amrasca biguttela biguttela, and whitefly, Bemisia tabaci and their predators in okra agroecosystem. Thiamethoxam 25% WG 25 g a.i./ha (84.71-91.73, 94.12 -98.11% reduction over control) was highly effective against aphid, whitefly and leaf hoppers which was on par with 50 g a.i./ ha (64.28 -76.90, 83.70 -87.92% reduction over control) and 75 g a.i./ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…These results shows that the relative preference of leafhopper changes with the stages of the crop. These findings are in line with Senapati and Khan (1978) who reported that okra at 7-14 weeks was most suitable for leafhopper and plant around maturity stage appears to be more susceptile than other stages and also present findings are conformity with the Senapati and Mohanty (1980) increase in the population of leafhopper from second week of December reaching a peak during first week of January, there after it declined.…”
Section: Resultssupporting
confidence: 92%
“…These results shows that the relative preference of leafhopper changes with the stages of the crop. These findings are in line with Senapati and Khan (1978) who reported that okra at 7-14 weeks was most suitable for leafhopper and plant around maturity stage appears to be more susceptile than other stages and also present findings are conformity with the Senapati and Mohanty (1980) increase in the population of leafhopper from second week of December reaching a peak during first week of January, there after it declined.…”
Section: Resultssupporting
confidence: 92%
“…Kalyan et al [12] also reported NSKE 5% comparatively higher per cent reduction in population of whiteflies in compared to entomopathogenic fungus. Ramarethinam et al [13], Naik and Shekharappa [14], Naik et al [10] and Saha [15] also reported V. lecanii to be effective against whitefly population and other homopterous, which corroborate the present findings.…”
Section: Effect Of Biopesticides Against Whitefly (Bemisia Tabaci Gen...supporting
confidence: 90%
“…Pandey (2018) found that thiamethoxam 25 WG @ 0.006% was effective against aphids, leaf hoppers, and white fly on okra plants. Also, Karthik et al (2020) found that thiamethoxam 25% WG at 25 g a.i. /ha was highly effective against whitefly after the first and second spray and minimized the spraying numbers, so that, it reduces environmental pollution and human hazards, as well as to compare seed treatment and foliar spraying.…”
Section: Discussionmentioning
confidence: 96%
“…Also, Liang et al (2015) found that thiamethoxam significantly reduced the average number of aphids on plants. Recently, Karthik et al (2020) found that thiamethoxam 25% WG at 25 g a.i. /ha was highly effective against whitefly after the first and second spray and minimized the spraying numbers, so that, it reduces environmental pollution and human hazards.…”
Section: Thiamethoxam Residues and Disappearance In Tomato Fruitsmentioning
confidence: 99%